Re-examining Social Mobility: Migrants' Relationally, Temporally, and Spatially Embedded Mobility Trajectories. (April 2022) - Boese, Martina; Moran, Anthony; Mallman, Mark
Social mobility research mainly investigates directional change in socio-economic circumstance. This article contributes to the strand of social mobility research that examines subjective experiences of economic movement. It analyses social mobility as a set of relationally, temporally and spatially embedded social practices, subjectively experienced and interpreted. The interactive nexus between social and spatial mobility is a fruitful line of inquiry, and the experiences of international migrants are distinctly suited for developing this analysis. Drawing on a qualitative study of migrants' mobilities, both social and spatial, post-arrival in Australia, we argue that social mobility is experienced as sets of contingent social practices. These in/variably co-exist with aspirations for a sense of belonging and connectedness, a sense of security and other non-economic needs and desires and are also always adjusted over time. In addition, migrants' status as legal, cultural or social Others shapes the experience of social mobility in distinctive ways.